Penerapan Metode PIECES Dalam Perbaikan Sistem Informasi Penjualan Berbasis Website Pada PT. Superspring Cabang Bandung - Fresa Dwi Juniar Sofalina (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2022)
This research is motivated by the sales system that exists at PT. Superspring Bandung is still done semi-manually where it is felt that it is not effective enough to support business activities at PT. Superspring Bandung, known to PT. Superspring Bandung is a company engaged in GPS tracker marketing technology. Ideally, a technology company is able to implement an integrated information system so that business processes can run well. This research uses quantitative and qualitative methods. Where the data collected by questionnaire and interview techniques. Respondents in this study were divided into two, namely external respondents and also internal respondents where external respondents were taken as a sample of 136 respondents and internal parties as many as 3 respondents. The analysis used in this study uses the PIECES method where from the results of the initial analysis it can be seen that the current system is not effective enough according to the indicators of the PIECES method. So that from this analysis a design is made that can improve the system. The design is made using the waterfall method, where from the results of system improvements, it can be seen that updating the system can support the company's activities properly. This is known from the results of usability testing with the Likert method as an indicator for calculating the results. From the calculations above, it can be concluded that the PIECES method used as the basis of the research is considered effective enough for companies to find out the deficiencies of the existing and ongoing systems.